The Role of a Tax Legal Specialist within South African Revenue Service during initiation of Tax Audits - Masehela, Kgabo, Freddy; Costa, King (My University, 2021)
The problem of tax compliance and tax evasion continually results in a plethora of impediments for tax regulators in South Africa and globally. An alarming number of corporate governance scandals always have an element of tax compliance issues in them. The state of unresolved SARS Audit cases, costly litigations and prolonged arbitration from the tax Ombudsman is an issue of concern and subject of this study. This is further exacerbated by technicalities emanating from legal perspectives, statutory dimensions, and regulatory frameworks. It is for this reason that this seeks to answer the question “What is the role of a tax legal specialist within SARS during initiation of tax audits?” A comprehensive literature analysis, hinged upon mapping review, which is a typology of systematic methodology was conducted to respond to the above-mentioned research question. Mapping reviews are useful when researchers seek to understand literature on a particular phenomenon which might provide a basis for further investigation. The inclusion/exclusion criteria required articles to be between 2014 and 2020 and were supposed to be focused on tax evasion, tax avoidance and current means to combat these classified fraud activities. This resulted in 10 studies included as part of the review. Analysis followed thematic approaches using the COSTA QDA Technique on webQDA cloud-computing software. The study found out that effectiveness and efficiency tax audits was handicapped by lack of competent tax legal audit specialist.
Keywords: Tax Authority; Tax Audit; SARS; Taxpayers; Legal tax audit specialist